An Innovative Behavioral Health Workforce Initiative: Keeping Pace with an Emerging Model of Care. (17th July 2017) - Putney, Jennifer M.; Sankar, Suzanne; Harriman, Kim K.; O'Brien, Kimberly H. McManama; Robinson, David Stanton; Hecker, Suzanne
ABSTRACT: Recent policy shifts in health care have created opportunities for social workers to provide services in integrated primary care and behavioral health settings. However, traditionally prepared social workers may not have the skill set necessary to meet practice demands. This article describes a behavioral health workforce initiative that trains master's of social work students for work in integrated primary care settings with children, adolescents, and transition-age youths. The training model includes field placements in integrated care settings, co-curricular seminars, and advanced clinical electives. This article identifies challenges of creating new field placements and developing new curricula to support students' acquisition of knowledge and skills required in integrated care settings. Additionally, it presents data on changes in students' knowledge and confidence.